2004
DOI: 10.1016/j.lwt.2004.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and chemical quality of ground beef treated with sodium lactate and sodium chloride during refrigerated storage

Abstract: The effects of sodium lactate (NaL) and sodium chloride (NaCl), either alone (30 g/kg) or in combination (20+20 g/kg), on the microbiological and chemical quality of raw ground beef during vacuum-packaged storage at 2 degrees C were investigated. The results showed that addition of NaL alone or in combination with NaCl significantly delayed the proliferation of aerobic plate counts, psychrotrophic counts, lactic acid bacteria and Enterobacteriaceae and extended the shelf life of the product up to 15 and 21 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 23 publications
(40 reference statements)
7
45
2
1
Order By: Relevance
“…No significant inhibitory effect on psycrotrophic counts in NaL treated ground beef at refrigerated storage was reported by Egbert, Huffman, Chen, and Jones (1992), in contrast to the findings of Sallam and Samejima (2004) on vacuum packaged ground beef. Likewise, a significant inhibitory effect on LAB had been reported in vacuum packaged pork sausages stored at 4 C (Brewer, McKeith, & Sprouls, 1993) and cooked pork sausages stored at 10 C (Sameshima, Takeshita, Miki, Itoh, & Kondo, 1998).…”
Section: Saltcontrasting
confidence: 64%
See 2 more Smart Citations
“…No significant inhibitory effect on psycrotrophic counts in NaL treated ground beef at refrigerated storage was reported by Egbert, Huffman, Chen, and Jones (1992), in contrast to the findings of Sallam and Samejima (2004) on vacuum packaged ground beef. Likewise, a significant inhibitory effect on LAB had been reported in vacuum packaged pork sausages stored at 4 C (Brewer, McKeith, & Sprouls, 1993) and cooked pork sausages stored at 10 C (Sameshima, Takeshita, Miki, Itoh, & Kondo, 1998).…”
Section: Saltcontrasting
confidence: 64%
“…Conversely, it was reported that LAB dominated the microbial flora in NaL cured beef during vacuum-packaged storage at 0 C (Papadopoulos, Miller, Acuff, Vanderzant, & Cross, 1991), as well as in frankfurter type sausages treated with NaL and stored at 0e4 C (Zivkovic, Radulovic, Ivanovic, Perunovic, & Dzinic, 2001). Sallam and Samejima (2004) found no significant effect on LAB when ground beef was treated with NaL alone, but a combination of NaL and NaCl resulted in >3 log units lower LAB counts after 21 days storage at 2 C compared to the untreated control, and 2.5 and 2.0 log units, respectively, compared to NaCl and NaL treated samples. NaL significantly delayed toxigenesis of C. botulinum in vacuum packaged beef, chicken, and salmon, although salmon required higher concentration or lower storage temperature than the former two products to give similar effect (Meng & Genigeorgis, 1994), indicating that results from meat studies cannot be easily transferred to fish and CSS.…”
Section: Saltmentioning
confidence: 71%
See 1 more Smart Citation
“…Although sodium chloride has long been used as a preservative in meats due to its ability of inhibiting microbial growth by restricting the available water, in these samples, NaCl concentration seems to be not high enough to show this effect. Accordingly, Sallam and Samejima (2004) reported that addition of NaCl alone (3%) did not have a significant effect on aerobic microorganisms. On the other hand, O'Connor et al (1993) argued that NaCl should be added in combination with other additives, such us lactates, in order to successfully preserve refrigerated products.…”
Section: Microbial Countsmentioning
confidence: 99%
“…Improvements in the shelf-life of oysters can have an important economic impact by reducing losses and by allowing the products to reach distant and new markets (Rhodehamel, 1992). Minimizing product contamination and delaying or inhibiting growth of spoilage microorganisms in fresh seafood are two major keys in improving shelf-life (Sallam & Samejima, 2004).…”
Section: Introductionmentioning
confidence: 99%